Ventilator-Associated Pneumonia and Its Pathogen in Intensive Unit Care : Second Leading Cause of Infection in ICU - Putu Diwyandaani Priyahita (Faculty of Medicine, Universitas Mataram, 2023)
Abstract: Ventilator-Associated Pneumonia is pneumonia that appears in patients after at least 48 hours using a mechanical ventilator. Ventilator-Associated Pneumonia (VAP) often occurs in the Intensive Care Unit (ICU) and is the second leading cause of infection in the ICU. Several researches in Indonesia shown a high prevalence and mortality rate in this type of Hospital Acquired Infections in ICU. Known risk factor of VAP are duration of ventilator, primary diagnosis, and comorbid such as Chronic Obstructive Pulmonary Disease. Pathogens also determined the severity of VAP and it was mostly caused by multi-drug resistant organism (MDRO) such as Acinetobacter baumanni, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Specimen culture needed to identify the causative pathogens and to determine the most effective antibiotic therapy, as the prognosis of VAP depend on the use of definite antibiotics and a quick treatment.